Marginal adaptation and performance of bioactive dental restorative materials in deciduous and young permanent teeth - Elizabeta Gjorgievska; John W. Nicholson; Snezana Iljovska; Ian J. Slipper (University of São Paulo, 2008)
OBJECTIVE: The aim of this study was to investigate the adaptation of different types of restorations towards deciduous and young permanent teeth. MATERIAL AND METHODS: Class V cavities were prepared in deciduous and young permanent teeth and filled with different materials (a conventional glass-ionomer, a resin-modified glass-ionomer, a poly-acid-modified composite resin and a conventional composite resin). Specimens were aged in artificial saliva for 1, 6, 12 and 18 months, then examined by SEM. RESULTS: The composite resin and the polyacid-modified composite had better marginal adaptation than the glass-ionomers, though microcracks developed in the enamel of the tooth. The glass-ionomers showed inferior marginal quality and durability, but no microcracking of the enamel. The margins of the resin-modified glass-ionomer were slightly superior to the conventional glass-ionomer. Conditioning improved the adaptation of the composite resin, but the type of tooth made little or no difference to the performance of the restorative material. All materials were associated with the formation of crystals in the gaps between the filling and the tooth; the quantity and shape of these crystals varied with the material. CONCLUSIONS: Resin-based materials are generally better at forming sound, durable margins in deciduous and young permanent teeth than cements, but are associated with microcracks in the enamel. All fluoride-releasing materials give rise to crystalline deposits.